Consumers' preference of nutritional label formats. - Talavera, M. T. M. (Compendium of Human Ecology Researches in the Philippines, 2003)
This cross-sectional study was conducted to determine the preference of consumers, who are predominantly mothers, on nutritional label formats. The study also explored the opinions of consumers regarding voluntary or mandatory labelling of general foods. A total of 185 respondents were randomly selected in 14 barangays in a semi-urban municipality. The results were presented from consumers' characteristics to knowledge of consumers on nutrition labels to preference for nutrition label format, and factors that affect consumers' knowledge and use of nutrition label. The consumers were mostly females belonging to the age group 21-50 years; majority of whom were married (94.1%), reached or finished secondary education (39.5%); and belonged to households with a family size of 5. Majority (67.6%) of them preferred the nutrition label to be located at the back of pack (BOP). Most of the consumers also preferred format D (healthy logo). Of the factors studied, except for income, other factors were not significantly associated with the preference of format of nutrition labels.